Establishment and characterization of a bona fide Barrett esophagus-associated adenocarcinoma cell line - Alvarez, Hector (2008)
Esophageal adenocarcinoma currently has one of the most rapidly increasing tumor incidences in the United States, with the vast majority of cases occurring on the backdrop of metaplastic epithelium (Barrett esophagus). The availability of appropriate cell line models is essential for maintaining the pace of esophageal cancer research and for pre-clinical validation of new therapeutic modalities. The identity of several of the widely utilized esophageal adenocarcinoma cell lines (BIC-1, SEG-1 and TE-7) have recently been called into question. Here we describe the establishment and characterization of a bona fide esophageal cancer cell line, JH-EsoAd1, from a patient with Barrett-associated adenocarcinoma. The rapid dissemination of this cancer cell line to the esophageal cancer research community should help ameliorate the current scarcity of preclinical models in this disease.